2008
DOI: 10.1111/j.1440-0960.2008.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Annular lesions in Kawasaki disease: A cause of confusion

Abstract: We present three cases of Kawasaki disease in which an annular eruption was the predominant cutaneous finding. The provisional diagnosis was Stevens-Johnson syndrome. However, the annular lesions were not typical of Stevens-Johnson syndrome: the lips were crusted without mucosal ulceration and the conjunctivitis was non-purulent without corneal erosions. Dermatologists are often involved in the initial assessment of this multisystem disease and should be aware of the variety of cutaneous manifestations, as rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This finding is compatible with Kawasaki disease, where ECG may show arrhythmia, prolonged PR interval, or non specific ST and T wave changes [1]. Finally, we demonstrated previous streptococcus pyogenes infection and we hypothesized it as a trigger for Kawasaki disease development, as previously described [14,18]. An infectious trigger of Kawasaki disease has been suspected by the epidemiologic features, such as age of affected children, seasonality of cases, and occurrence of community outbreaks and epidemics [1]; however, no known infectious agent has been consistently found [19].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding is compatible with Kawasaki disease, where ECG may show arrhythmia, prolonged PR interval, or non specific ST and T wave changes [1]. Finally, we demonstrated previous streptococcus pyogenes infection and we hypothesized it as a trigger for Kawasaki disease development, as previously described [14,18]. An infectious trigger of Kawasaki disease has been suspected by the epidemiologic features, such as age of affected children, seasonality of cases, and occurrence of community outbreaks and epidemics [1]; however, no known infectious agent has been consistently found [19].…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, erythema multiforme was reported as a cutaneous manifestation of classic Kawasaki disease in only 2 young children, a 22-month-old girl in 1979 [9] and a 16-month-old boy in 2010 [10]. In addition, other 3 patients were described affected by Kawasaki disease associated to annular lesions [14]. To our knowledge, this is the first report of erythema multiforme as first sign of incomplete Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%
“…Annular lesions have not been well described in the literature in KD, and even in the initial case series observed by Kawasaki, there is no mention of them. We found only four cases reported; two patients observed by Ming and Wargon (3) had annular lesions associated with conjunctival injection and crusted hemorrhagic lips, similar to the clinical picture of a Stevens‐Johnson syndrome, whereas another child observed by the same authors (3) and a case reported by Tsai and colleagues (4) had annular lesions studded with pustules, raising the question of an association with psoriasis. To the best of our knowledge, ours is the first case of KD in which the cutaneous manifestations are exclusively asymptomatic annular lesions with central clearing and erythematous, firm, raised borders without scaling, vesicles, or crusts that mimic figurate inflammatory dermatoses of infancy.…”
Section: Discussionmentioning
confidence: 71%
“…One case, described as varicelliform, had outcroppings of painful pustulovesicular lesions on an indurated and erythematous base as the predominant lesion . Annular lesions with and without pustules in the presence of splinter hemorrhages have also been documented .…”
Section: Discussionmentioning
confidence: 99%